2004
DOI: 10.1021/bi048438p
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structure of Transcription Factor Sp1 DNA Binding Domain,

Abstract: To understand the DNA recognition mechanism of zinc finger motifs of transcription factor Sp1, we have determined the solution structure of DNA-binding domain of the Sp1 by solution NMR techniques. The DNA-binding domain of Sp1 consists of three Cys(2)His(2)-type zinc finger motifs. They have typical betabetaalpha zinc finger folds and relatively random orientations. From DNA-binding analysis performed by NMR and comparison between structures determined here and previously reported structures of other zinc fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 33 publications
9
91
0
2
Order By: Relevance
“…S7. The human Sp1 ZF-DBD (Sp1 residue 616-709) comprising three ZFs was expressed in E. coli strain BL21(DE3) via a pET-49b-derivative plasmid and chromatographically purified using cation-exchange and size-exclusion chromatography as described (57 N-labeled Egr-1 ZF-DBDs with 28-bp DNA duplexes were prepared as described previously (28). For each sample of the complexes, the molar ratio of protein to DNA was 1:2 to ensure the DNA-bound states of the isotope-labeled proteins.…”
Section: Methodsmentioning
confidence: 99%
“…S7. The human Sp1 ZF-DBD (Sp1 residue 616-709) comprising three ZFs was expressed in E. coli strain BL21(DE3) via a pET-49b-derivative plasmid and chromatographically purified using cation-exchange and size-exclusion chromatography as described (57 N-labeled Egr-1 ZF-DBDs with 28-bp DNA duplexes were prepared as described previously (28). For each sample of the complexes, the molar ratio of protein to DNA was 1:2 to ensure the DNA-bound states of the isotope-labeled proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Sumoylation of KLF3 at K10 and K197 is required for full repressor activity. analysis of SP1 (22), it is known that C2H2 zinc fingers consist of two antiparallel b-sheets and an a-helix, with these structures being co-ordinated and stabilized by the zinc ion. The a-helix of each finger makes contact with the major groove of DNA, with specific residues binding to guanine-rich three base pair sites (21).…”
Section: The Structure and Molecular Interactions Of Klf3mentioning
confidence: 99%
“…This finger is 23 amino acids long and residues K273, H276, and A279 of human KLF3 are predicted to make primary contact with DNA, having a preference for the sequence NGA/G. Three-dimensional NMR analysis of SP1 (22) and mutagenesis studies have indicated that finger 1 may have reduced DNA contact and contribute least to binding affinity and specificity (23).…”
Section: The Structure and Molecular Interactions Of Klf3mentioning
confidence: 99%
“…The EMSA technique measures the capacity of control and treated Sp1 to bind to a cognate DNA binding site, in this case one of the Sp1 recognition sequences (GC-1) in the sodium glucose co-transporter 1 gene of mouse kidney [25]. Zn-finger mini-domains depend upon structural Zn 2+ to establish their correct DNA-binding conformation [4,34]. Thus, the loss of DNA binding activity resulting from reaction with competing Zn 2+ binding ligands can be attributed to peptide unfolding in the absence of Zn 2+ .…”
Section: Reaction Of Specific Zn-protein Zn 3 -Sp1 With Apo-mt Gshmentioning
confidence: 99%
“…Besides its role as a component of enzyme active sites it also provides critical structural stabilization to a multitude of proteins, including a multitude of zinc-finger transcription factors [3,4]. Despite its familiar role in protein structure and function, relatively little is known about Zn 2+ trafficking that brings Zn 2+ to such sites.…”
Section: Introductionmentioning
confidence: 99%